(2E)-3-(4-Methylphenyl)-1-(2-methyl-4-phenylquinolin-3-yl)prop-2-en-1-on e monohydrate - Prasath, R.; Sarveswari, S.; Vijayakumar, V.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The title hydrate, C26H21NO center dot H2O, exhibits significant twists of the benzene ring [dihedral angle = 87.24 (6)degrees] and chalcone residue [C-C-C-C torsion angle = -94.46 (17)degrees] out of the plane through the quinoline ring system. The conformation about the C C bond [1.341 (2) angstrom] is E. The solvent water molecule forms hydrogen bonds to carbonyl O and quinoline N atoms derived from two molecules and through the application of a centre of inversion, a 16-membered {center dot center dot center dot HOH center dot center dot center dot OC3N}(2) synthon is formed to stabilize the resulting tetrameric (two organic molecules plus two water molecules) aggregate. These are connected into a two-dimensional array via two C-H center dot center dot center dot O contacts, also involving the water molecule. The layers stack along the c axis, being linked by C-H center dot center dot center dot pi interactions.